KLAUS SCHWAB’S “THE FOURTH INDUSTRIAL REVOLUTION” AND THE DISCUSSION OF ISSUES RELATED TO ARTIFICIAL INTELLIGENCE - Muslimbek Alijanov (Bright Mind Publishing, 2025)
This article examines the issues related to artificial intelligence as discussed in Klaus Schwab’s book The Fourth Industrial Revolution.
Keywords: The Fourth Industrial Revolution, artificial intelligence, Klaus Schwab, technological development, social inequality, technological determinism, international diplomacy, global cooperation.